ACUTE AND SUBCHRONIC TOXICITY STUDY OF TUD-RAK-KA-SAI-PUU RECIPE IN RATS - Sireeratawong, Seewaboon; Nanna, Urarat; Vannasiri, Supaporn; Chiruntanat, Natthakarn; Srithiwong, Supachai; Subcharoen, Pennapa; Termwiset, Pornthip; Tungsukruthai, Parunkul; Chuthaputti, Anchalee; Jaijoy, Kanjana (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Acute and subchronic toxicities of Tud-Rak-Ka-Sai-Puu (TR) recipe were studied in male and female rats. After 14 days of a single oral administration of test substance (5,000 mg/kg body weight), measurement of the body and organs weights, necropsy and health monitoring were performed. No signs and differences in the weights and behavior were observed relative to the control rats, suggesting that TR recipe in the dose of 5,000 mg/kg body weight does not produce acute toxicity. The subchronic toxicity was determined by oral feeding in male and female rats daily with the test substance at 2, 20, 200 and 2,000 mg/kg body weight for 90 days. No defects of animal behavior were observed in the test groups. Both test and control groups (on the 90th day) as well as the satellite group (on the 118th day) were analyzed by measuring their final body and organ weights, taking necropsy, and examining hematology, blood clinical chemistry, and microanatomy. These results together with the information of signs, behavior and health monitoring can lead to a conclusion that an oral administration of TR recipe at 2, 20, 200 and 2,000 mg/kg body weight for 90 days did not cause subchronic toxicity.